Snake species richness predicts breeding distribution of short-toed snake eagle in central Italy. Issue 2 (4th March 2018) - Cecere, Jacopo G.; Panuccio, Michele; Ghiurghi, Andrea; Urbano, Ferdinando; Imperio, Simona; Celada, Claudio; López-López, Pascual
Abstract : Birds of prey, as top predators, play a key role in ecosystem functioning by regulating prey populations and, by means of cascade effects, promoting biodiversity. This makes them adequate sentinels of ecosystem health. Here we analyse the relationship between the occurrence of breeding short-toed snake eagle ( Circaetus gallicus ) and both the richness of potential prey species and landscape characteristics by taking into account two different spatial scales (i.e. nest-site scale and landscape scale). The short-toed snake eagle offers an interesting case study for investigating the relationships between top predators, prey diversity, and habitats, because it is an extremely specialised raptor that feeds on mesopredators, mostly snakes. Additionally, short-toed snake eagles are mainly threatened by changes in agriculture and land use in Europe, which have reduced the extent of suitable hunting habitats, and by the decrease in snake populations. Our study was conducted in the Latium Region (central Italy) in 2007, where most of the Italian breeding population is concentrated. By means of habitat selection analyses using generalised linear models, our results showed that the species selected breeding areas characterised by low elevations, rugged slopes, and high snake species richness at the nest-site scale (1 km 2 ). At the landscape scale (25 km 2 ), the best model showed that birds selected areas characterised by lower elevations for nesting, with a tendency towards intermediate values of wood cover and high snake species richness. Our study highlights the strong relationship between snake species richness and the occurrence of breeding eagles at both spatial scales, with optimal breeding sites located closer to hunting areas than expected by chance. This study provides further support for the role of short-toed snake eagles as sentinel species for Mediterranean habitats, and highlights the link between the location of nesting sites and the occurrence of human-modified landscapes characterised by high prey richness.